La motivación de los decretos judiciales. Principios para determinar qué decretos deben motivarse - Rodríguez-Ocaña, Rafael ("Iustitia et iudicium" ; 4, 2010)
Judical decrees are pronouncements that are different from the sentence. They can be classified from different points of view, although the CIC does not offer an explicit division. The legislator prescribes the need to express the reasons - at least in a summary fashion or refer to reasons expressed in another act - for all types of decrees exept those that are merely procedural. This article explains the doctrinal principles which show the motivation of a particular judicial decree